Hubungan pengetahuan, paritas dan dukungan suami terhadap penggunaan kontrasepsi implant di Kota Kendari tahun 2023 - Andriani, Asri; Sabilu, Yusuf; Liaran, Rastika Dwiyanti (Indonesian Journal of Health Science, 2024)
Introduction Based on data from the Southeast Sulawesi Provincial Health Office regarding the use of implantable contraceptives from 2019 to 2022, it shows that there are 441,180 active acceptors and 29,153 implantable contraceptives.  The use of implantable contraceptives in the city of Kendari from 2019 to 2022 shows that there are 44,991 active acceptors and 1,944 contraceptives. This study aims to find out the relationship between knowledge, parity, and support of husbands for implant contraceptive users at the UPTD Kemaraya Health Center in 2023. Methods: This type of research is quantitative using a cross sectional design. The total population in this study was 198 respondents. Sampling used total sampling. Data analysis used univariate and bivariate analysis with the chi-square tes. Results: The results of the study showed that there was no connection of parity (p=0.645) on the use of contraceptive implants at the Kemaraya Community Health Center UPTD. Meanwhile, there is a relationship between knowledge (p=0.004), husband's support (p=0.003) on the use of contraceptive implants at the Kemaraya Health Center UPTD. Conclusions: Based on the results of this study, it is hoped that it can immediately provide complete information about contraception to family planning acceptors and organize various programs such as increasing counseling on types of contraception so that family planning acceptors can choose the most appropriate contraception according to their needs and conditions. Pendahuluan: Berdasarkan data dinas Kesehatan provinsi Sulawesi Tenggara tentang penggunaan kontrasepsi implant pada tahun 2019 sampai tahun 2022 menunjukan bahwa akseptor aktif sebanyak 441.180 dan kontrasepsi implant sebanyak 29.153.  Penggunaan kontrasepsi implant di kota Kendari pada tahun 2019 sampai tahun 2022 menunjukan bahwa akseptor aktif sebanyak 44.991 dan kontrasepsi sebanyak 1.944. Penelitian ini bertujuan ntuk mengetahui hubungan pengetahuan, paritas dan dukungan suami terhadap pengguna kontrasepsi implant di UPTD Puskesmas Kemaraya Tahun 2023. Metode: Jenis penelitian ini adalah kuantitatif dengan menggunakan desain cross sectional. Jumlah populasi pada penelitian ini yakni sebanyak 198 responden. Pengambilan sampel menggunakan total sampling.  Analisis data menggunakan analisis univariat dengan bivariat dengan uji chi-square. Hasil:  Hasil penelitian menunjukan tidak ada hubungan paritas (p=0,645) terhadap penggunaan kontrasepsi implant di UPTD Puskesmas Kemaraya. Sedangkan ada hubungan pengetahuan (p=0,004), dukungan suami (p=0,003) terhadap penggunaan kontrasepsi implant di UPTD Puskesmas Kemaraya. Kesimpulan: Berdasarkan hasil penelitian ini, diharapkan dapat segera memberikan informasi lengkap tentang kontrasepsi kepada akseptor keluarga berencana dan menyelenggarakan berbagai program seperti meningkatkan penyuluhan jenis-jenis kontrasepsi sehingga akseptor KB dapat memilih kontrasepsi yang paling tepat sesuai dengan kebutuhan dan kondisinya.